A desensitizing agent for tooth enamel repair and its preparation method
This tooth enamel repair medication, formulated with specific ingredients, solves the problem of separation between enamel repair and desensitization effects. It achieves a triple effect of physical sealing, nerve inhibition, and active mineralization, forming a long-lasting protective layer suitable for both enamel repair and desensitization.
Patent Information
- Application Number
- CN202511598245.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2026-01-30
- Estimated Expiration
- 2045-11-04
AI Technical Summary
Existing enamel restorations suffer from a disconnect between physical enamel repair and desensitization, poor bioadhesion, and short-lasting effects. Traditional medications struggle to simultaneously achieve the triple benefits of physical sealing, nerve inhibition, and active mineralization.
The product is formulated by combining chitosan quaternary ammonium salt modified with paeonol-dopamine, enzyme-responsive precursor minerals, polyethylene glycol didopamine-modified hydroxyapatite, strontium nitrate, hyaluronic acid-maleimide, and L-cysteine in a specific ratio to form a repair desensitizing gel with strong adhesion and enzyme responsiveness, achieving the triple effects of physical sealing, nerve inhibition, and active mineralization.
This gel forms a long-lasting protective layer on the tooth surface, quickly relieving sensitivity and achieving strong adhesion, dense sealing, and continuous mineralization. It is durable, resistant to brushing and acid corrosion, and is suitable as a routine desensitization solution.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biological medicine, and particularly relates to a desensitizing medicament for enamel repair and a preparation method thereof. BACKGROUND
[0002] Under normal circumstances, enamel covers dentin, and isolates external stimuli from the pulp nerve; when enamel is defective, dentin is exposed, and the dentin tubules in the dentin become a channel for external stimuli to conduct to the pulp. The currently recognized mechanism of tooth sensitivity is mainly the fluid dynamics theory: external stimuli will cause rapid flow of liquid in the dentin tubules, such as cold stimulation causing liquid contraction and mechanical pressure causing liquid extrusion, and such flow will pull the nerve endings on the surface of the pulp, causing transient and sharp pain. Therefore, the core logic of desensitizing medicaments can be summarized into two categories: one is physical sealing, by forming a protective layer on the surface of the dentin or in the tubules, to block the flow of liquid; the other is nerve inhibition, by acting on the nerve endings of the pulp, to reduce their sensitivity to stimulation.
[0003] Early ways to relieve tooth sensitivity mainly focus on symptomatic care, such as using fluoride toothpaste to promote enamel remineralization and enhance acid resistance through fluoride ions, but the desensitizing effect on exposed dentin is limited; or avoiding stimulating food, using soft bristle toothbrushes, etc., which can only assist in prevention and cannot specifically address the sensitivity caused by dentin exposure. Subsequently, topical agents such as gels containing potassium nitrate and strontium chloride appeared, which can temporarily block dentin tubules or inhibit nerves through ion action, but the effect lasts for only a few hours to a few days. In addition, invasive methods such as resin filling and laser treatment have been used in dental clinics, the former is suitable for cases with large enamel defects, but has poor applicability for small defects or extensive sensitive areas; the latter can seal the tubules through laser heat effect, but the treatment cost is high and there is postoperative discomfort, making it difficult to be popularized as a routine desensitizing solution.
[0004] With the deepening of the combination of material science and dentistry, the desensitizing drugs for enamel repair gradually develop towards the integration of repair and desensitization. The first stage takes the remineralization agent as the core, and the representative components include sodium fluoride, sodium monofluorophosphate, casein phosphopeptide-amorphous calcium phosphate, etc. Among them, casein phosphopeptide-amorphous calcium phosphate can simulate the mineral composition in saliva, and through the carrier effect of casein phosphopeptide, it can accurately transport calcium and phosphorus ions to the enamel demineralization area, fill the surface pores, and at the same time, fluoride ions can replace the hydroxyl groups in the crystal to form more stable fluorapatite, enhancing the acid resistance of enamel. Although this kind of drug can achieve the initial repair of enamel, the desensitizing effect depends on the indirect sealing of the mineralization layer to the tubule, and the effect on severe sensitive population is limited. The technical breakthrough of the second stage is the application of composite desensitizing components, that is, the addition of nerve inhibiting components to achieve double action. For example, desensitizing drugs containing strontium fluoride, strontium ions can bind to collagen in dentin tubules to form insoluble strontium phosphate salt, physically blocking the tubule; on the other hand, it can act on the potassium ion channel of dental pulp nerve to inhibit nerve signal transmission, relieving sensitivity from channel blocking and nerve inhibition. In addition, some drugs introduce components such as zinc oxide and calcium hydroxide, which can neutralize the acidic substances in the mouth through the alkaline environment, reduce further demineralization of enamel, and create favorable conditions for repair; although the drug significantly improves the durability of desensitizing effect, enamel repair is still mainly based on surface mineralization, and it is difficult to repair deep enamel defects or cracks. SUMMARY
[0005] In view of the problems of separation of enamel repair and dentin desensitization effect, poor bioadhesion, and short-acting effect in the prior art, the present application provides a desensitizing drug for enamel repair and a preparation method thereof, which uses a specific proportion of components such as paeonol-dopamine modified chitosan quaternary ammonium salt, enzyme-responsive precursor mineral, polyethylene glycol di-dopamine modified hydroxyapatite, strontium nitrate, hyaluronic acid-maleimide, and L-cysteine to obtain a repair desensitizing gel with strong adhesion and enzyme responsiveness. The gel can form a long-acting protective layer on the tooth surface, and at the same time realize the triple effects of physical sealing, nerve inhibition and active mineralization. The specific technical scheme is as follows:
[0006] The enamel restoration desensitizing medicine comprises the following raw materials in mass fraction: 3-5 parts of dopamine-modified quaternary ammonium salt of cortex phellodendri and dopamine-modified chitosan, 4-6 parts of enzyme-responsive precursor mineral, 2-3 parts of polyethylene glycol di-dopamine modified hydroxyapatite, 1-2 parts of strontium nitrate, 1.5-2.5 parts of hyaluronic acid-maleimide, 0.3-0.6 parts of L-cysteine, 0.8-1.2 parts of carbomer, 14-17 parts of glycerol and 65-72 parts of deionized water; the pH value of the medicine is adjusted to 6.5-7.0; the dopamine-modified quaternary ammonium salt of cortex phellodendri and dopamine-modified chitosan is obtained by modifying chitosan quaternary ammonium salt with cortex phellodendri and dopamine hydrochloride under the catalysis of tyrosinase; the mass ratio of dopamine hydrochloride to cortex phellodendri is (2-3):(4-5); the enzyme-responsive precursor mineral is obtained by coating nano-pyrophosphate calcium with epsilon-polylysine; and the polyethylene glycol di-dopamine modified hydroxyapatite is obtained by modifying hydroxyapatite with polyethylene glycol di-dopamine on the surface.
[0007] In the above medicine, the preparation method of the dopamine-modified quaternary ammonium salt of cortex phellodendri and dopamine-modified chitosan comprises the following steps: preparing 1g / 100mL-1.5g / 100mL chitosan quaternary ammonium salt solution with PBS buffer solution with pH=6.0-6.5; preparing dopamine-hopea mixture solution containing 2g / 100mL-3g / 100mL dopamine hydrochloride and 4g / 100mL-5g / 100mL cortex phellodendri with anhydrous ethanol; preparing 0.4g / 100mL-0.6g / 100mL tyrosinase solution with PBS buffer solution with pH=6.0-6.5; under the protection of light and nitrogen, adding the dopamine-hopea ethanol solution and the tyrosinase solution into the chitosan quaternary ammonium salt solution according to the volume ratio of 100:(20-25):(3-5), stirring at 37-40℃; heating to inactivate the enzyme; cooling to room temperature, loading into a dialysis bag, using deionized water containing 1%-2% volume ethanol as dialysate, dialyzing for 72-96h; then dialyzing with flowing deionized water; and freeze-drying to obtain the dopamine-modified quaternary ammonium salt of cortex phellodendri and dopamine-modified chitosan.
[0008] In the above preparation method of the dopamine-modified quaternary ammonium salt of cortex phellodendri and dopamine-modified chitosan, the stirring is 200rpm-300rpm for 24-30h; the enzyme inactivation by heating is heating to 80-85℃ for 10-15min; the molecular weight cut-off of the dialysis bag is 3500Da; the dialysate is replaced every 8-12h; and the dialysis with flowing deionized water is 8-12h.
[0009] The preparation method of the enzyme-responsive precursor mineral in the above medicine comprises the following steps: preparing a nano-calcium pyrophosphate suspension of 5g / 100mL-10g / 100mL with deionized water, filtering with a filter membrane after ultrasonic dispersion to obtain an inner phase; preparing an ε-polylysine solution of 2g / 100mL-5g / 100mL with deionized water, adjusting the pH value to 7.2-7.5 to obtain an outer phase; under the condition of ice water bath and stirring, the inner phase is added into the outer phase at a volume ratio of 1: (1.05-1.2), and stirring is performed for 1h-1.5h; the precipitate is obtained by centrifugation, and the precipitate is washed by centrifugation with ultrapure water and freeze-dried to obtain the enzyme-responsive precursor mineral.
[0010] In the preparation method of the enzyme-responsive precursor mineral, the filter membrane is a 0.45μm filter membrane; the pH value is adjusted by using a 0.5M-1M NaOH aqueous solution; the stirring speed is 600rpm-800rpm; the dropping speed is 1mL / min-2mL / min; and the ultrapure water is washed by centrifugation for 3-4 times.
[0011] In the above medicine, the preparation method of the polyethylene glycol doped polydopamine modified hydroxyapatite comprises the following steps: preparing a nano-hydroxyapatite dispersion liquid of 1.0g / 100mL-1.5g / 100mL with a Tris-HCl buffer solution with a pH value of 8.0-8.5; adding polyethylene glycol doped polydopamine with a mass fraction of 20%-25% of the nano-hydroxyapatite, ultrasonic mixing, and then stirring; collecting the precipitate by centrifugation, washing the precipitate, and freeze-drying to obtain the polyethylene glycol doped polydopamine modified hydroxyapatite.
[0012] In the preparation method of the polyethylene glycol doped polydopamine modified hydroxyapatite, the particle size D50 of the nano-hydroxyapatite is less than 100nm; the stirring is performed at 200rpm-300rpm under the conditions of 25℃-30℃ and light avoidance for 30h-35h; and the precipitate is washed once-twice with an ethanol aqueous solution and twice-three times with deionized water.
[0013] In the above medicine, the carbomer is carbomer 940.
[0014] The preparation method of the desensitizing medicine for tooth enamel repair comprises the following steps:
[0015] Deionized water, glycerol, hyaluronic acid-maleimide, danpi phenol-dopamine modified chitosan quaternary ammonium salt, enzyme-responsive precursor mineral, polyethylene glycol doped polydopamine modified hydroxyapatite, and strontium nitrate are mixed in mass fractions, and carbomer is added under stirring, and the stirring is continued to swell fully, the pH value is adjusted to 6.5-7.0, then L-cysteine is added, and stirring is performed for 1min-2min, and vacuum defoaming is performed to obtain the medicine.
[0016] In the above method for preparing the medicine, the pH value is adjusted by triethanolamine.
[0017] The desensitizing medicine for repairing tooth enamel and the preparation method thereof have the beneficial effects including:
[0018] Firstly, the medicine is modified by biomaterial functionalization and designed by multi-component synergy to realize adhesion, repair, desensitization, antibiosis and durability integration, and the core advantage is that:
[0019] (1) The problem of separation of traditional medicine repair and desensitization is solved: the triple effects of physical closure, nerve inhibition and active mineralization are realized; (2) The bottleneck of poor adhesion and short action is broken: the wet adhesion mechanism of hydrogen bond and electrostatic adsorption is used to make the medicine adhere to the dentin tubule and enamel defect, so as to avoid being washed away by saliva; (3) Intelligent response repair is realized: ALP triggers Ca 2+ release, and mineralization ions are provided on demand in the oral cavity, and hydroxyapatite is used to realize mineralization plugging; (4) The pH value of 6.5-7.0 matches the neutral environment of the oral cavity, has no irritation, has durability of resistance to washing and acid corrosion, and can be used as a conventional desensitization scheme.
[0020] Secondly, the effect of dopamine-modified chitosan quaternary ammonium salt: (1) Wet adhesion basis: dopamine o-diphenol forms a hydrogen bond with the hydroxyl group of dentin, and chitosan quaternary ammonium salt forms electrostatic adsorption with dentin, and the double effect ensures that the medicine is firmly attached to the wet tooth surface; (2) Antibacterial protection: Danpi phenol inhibits the reproduction of oral pathogenic bacteria, reduces the erosion of bacterial acid on the film layer and the tooth, and prolongs the repair effect; (3) Film support: Chitosan quaternary ammonium salt has film-forming property, which provides an attachment carrier for other functional components.
[0021] Thirdly, the effect of enzyme-responsive precursor mineral (ε-polylysine-coated nano-calcium pyrophosphate): (1) Intelligent mineralization: ALP in the oral cavity hydrolyzes calcium pyrophosphate to continuously release Ca 2+ , which provides raw materials for tooth enamel remineralization; (2) Particle stabilization: ε-polylysine coating prevents nano-calcium pyrophosphate from agglomerating, ensuring that the particles can penetrate into the dentin tubule and accurately release Ca 2+ ; (3) Auxiliary antibiosis: ε-polylysine itself has antibacterial properties, which cooperates with danpi phenol to improve the cleanliness of the oral microenvironment.
[0022] Four, the effect of polyethylene glycol doped hydroxyapatite dopamine: (1) direct repair: hydroxyapatite and tooth enamel composition consistent, can directly fill dentin tubules and enamel small defects, forming a physical seal layer; (2) dispersion and fixation: polyethylene glycol dopamine can improve the dispersibility of hydroxyapatite, avoid agglomeration; also can improve the adhesion of hydroxyapatite, reduce the shedding of hydroxyapatite; (3) shape adaptation: PEG chain has flexibility, can adapt to the irregular shape of dentin tubules, form a dense seal layer.
[0023] Five, the effect of strontium nitrate: strontium nitrate is a regular component of tooth desensitizer, strontium ions combine with collagen in dentin tubules to form insoluble strontium phosphate salt, physically blocking the tube; at the same time, it acts on the potassium ion channel of dental pulp nerve, inhibits nerve signal transmission, and reduces sensitivity; strontium ions can replace calcium ions in enamel crystals, enhancing the acid resistance of enamel.
[0024] Six, the effect of hyaluronic acid-maleimide and L-cysteine: (1) structure enhancement: hyaluronic acid-maleimide and L-cysteine can form a cross-linked network inside the gel, improving the toughness and mechanical strength of the membrane layer; (2) durability improvement: the cross-linked structure can resist physical friction and chemical erosion of acidic substances during brushing, prolonging the drug action time.
[0025] Seven, the effect of adjuvants: carbomer as gel matrix has excellent thixotropy, easy to spread when applied. Glycerin as humectant to prevent gel cracking, plasticizer to improve membrane flexibility and co-solvent to promote ingredient dissolution and dispersion, improving user comfort. pH adjustment can neutralize the acidity of carbomer to form a stable gel system; at the same time, it matches the neutral environment of the oral cavity, avoiding irritation to the gums and dental pulp.
[0026] Eight, the components of the drug in the present application form a synergistic effect through functional complementation and mechanism linkage:
[0027] (1) adhesion, sealing and mineralization synergy: the wet adhesion of modified chitosan provides a fixed platform for enzyme-responsive minerals and modified hydroxyapatite, ensuring that both are not washed away by saliva; modified hydroxyapatite directly blocks the tubules, sealing immediately, and enzyme-responsive minerals continuously release Ca 2+ , long-acting mineralization, forming a combination of immediate hole blocking and continuous repair, both quickly relieving sensitivity and fundamentally repairing enamel defects.
[0028] (2) desensitization, antibacterial and durability synergy: strontium nitrate physically blocks the tube and inhibits the nerve to quickly desensitize, and the combination of paeonol and ε-polylysine synergistically antibacterial, reducing further damage to the tooth by bacterial acid production, protecting the desensitization effect; the cross-linked network of hyaluronic acid-maleimide and L-cysteine enhances the mechanical strength of the membrane layer, resisting brushing and acid erosion, making the desensitization and antibacterial effects more durable.
[0029] (3) Component, structure and performance synergy: the polyethylene glycol chain of modified hydroxyapatite improves dispersibility, so that it can be uniformly distributed in the modified chitosan film layer; the modified hydroxyapatite is closely combined with the modified chitosan to avoid falling off; the cross-linked network further locks all components as a whole, forming an integrated system with firm adhesion, closed density, continuous mineralization and long-acting desensitization, and achieving good synergistic effect. DETAILED DESCRIPTION
[0030] The application will be further described below in combination with specific implementation cases, but the application is not limited to these examples.
[0031] Example 1
[0032] A desensitizing drug for enamel repair, the drug comprising the following raw materials in mass fraction: 4 parts of paeonol-dopamine modified chitosan quaternary ammonium salt, 5 parts of enzyme-responsive precursor mineral, 2.5 parts of polyethylene glycol di-dopamine modified hydroxyapatite, 1.5 parts of strontium nitrate, 2 parts of hyaluronic acid-maleimide, 0.5 parts of L-cysteine, 1 part of carbomer, 15 parts of glycerol and 70 parts of deionized water; the pH value of the drug is adjusted to 6.8. The paeonol-dopamine modified chitosan quaternary ammonium salt is obtained by modifying chitosan quaternary ammonium salt with paeonol and dopamine hydrochloride under the catalysis of tyrosinase; the mass ratio of dopamine hydrochloride to paeonol is 2.5:4.5; the enzyme-responsive precursor mineral is obtained by coating nano-calcium pyrophosphate with ε-polylysine; the polyethylene glycol di-dopamine modified hydroxyapatite is obtained by surface adhesion modification of hydroxyapatite with polyethylene glycol di-dopamine; the carbomer is carbomer 940.
[0033] The preparation method of the paeonol-dopamine modified chitosan quaternary ammonium salt comprises the following steps: preparing 1.2 g / 100 mL chitosan quaternary ammonium salt solution with PBS buffer solution with pH=6.2; preparing dopamine hydrochloride and paeonol mixed solution containing 2.5 g / 100 mL dopamine hydrochloride and 4.5 g / 100 mL paeonol with anhydrous ethanol; preparing 0.5 g / 100 mL tyrosinase solution with PBS buffer solution with pH=6.2; under light protection and nitrogen protection, adding the dopamine-paeonol ethanol solution and the tyrosinase solution into the chitosan quaternary ammonium salt solution according to the volume ratio of 100:23:4, stirring at 38℃ and 250 rpm for 26 h; increasing the temperature to 82℃ to inactivate the enzyme for 13 min; cooling to room temperature, loading into a dialysis bag with a molecular weight cut-off of 3500 Da, using deionized water containing 1.5% volume ethanol as dialysis solution, dialyzing for 80 h, replacing the dialysis solution every 10 h; then dialyzing for 10 h with flowing deionized water; freeze-drying to obtain the paeonol-dopamine modified quaternized chitosan.
[0034] The preparation method of the enzyme-responsive precursor mineral comprises the following steps: preparing a 8 g / 100 mL nano-calcium pyrophosphate suspension with deionized water, performing ultrasonic dispersion, and filtering with a 0.45 μm filter membrane to obtain an inner phase; preparing a 3 g / 100 mL ε-polylysine solution with deionized water, and adjusting the pH value to 7.4 with a 0.8 M NaOH aqueous solution to obtain an outer phase; under the condition of ice water bath and 700 rpm stirring, the inner phase is added to the outer phase at a volume ratio of 1:1.1, the adding speed is 1.5 mL / min, and the stirring is performed at 700 rpm for 1 h; the precipitate is obtained by centrifugation, washed with ultrapure water for 3 times, and freeze-dried to obtain the enzyme-responsive precursor mineral.
[0035] The preparation method of the polyethylene glycol doped dopamine modified hydroxyapatite comprises the following steps: preparing a 1.3 g / 100 mL nano-hydroxyapatite dispersion liquid with a pH 8.2 Tris-HCl buffer solution; adding 22% polyethylene glycol doped dopamine of the nano-hydroxyapatite mass, uniformly mixing by ultrasonic, and then stirring at 250 rpm for 32 h under the condition of 28℃ and light shielding; collecting the precipitate by centrifugation, washing the precipitate with an ethanol aqueous solution for 2 times, washing the precipitate with deionized water for 2 times, and freeze-drying to obtain the polyethylene glycol doped dopamine modified hydroxyapatite.
[0036] The preparation method of the above-mentioned desensitizing drug for enamel repair comprises the following steps:
[0037] Deionized water, glycerol, hyaluronic acid-maleimide, paeonol-dopamine modified chitosan quaternary ammonium salt, enzyme-responsive precursor mineral, polyethylene glycol doped dopamine modified hydroxyapatite and strontium nitrate are mixed according to the mass fraction, carbomer is added under stirring, the stirring is continuously performed to fully swell, the pH value is adjusted to 6.8 with triethanolamine, then L-cysteine is added, the stirring is performed for 1.5 min, vacuum defoaming is performed, and the drug is obtained.
[0038] Example 2
[0039] A desensitizing drug for enamel repair, the drug comprises the following raw materials in mass fraction: paeonol-dopamine modified chitosan quaternary ammonium salt 3 parts, enzyme-responsive precursor mineral 6 parts, polyethylene glycol doped dopamine modified hydroxyapatite 2 parts, strontium nitrate 2 parts, hyaluronic acid-maleimide 1.5 parts, L-cysteine 0.6 parts, carbomer 0.8 parts, glycerol 17 parts and deionized water 65 parts; the pH value of the drug is adjusted to 7.0. The paeonol-dopamine modified chitosan quaternary ammonium salt is obtained by modifying chitosan quaternary ammonium salt with paeonol and dopamine hydrochloride under the catalysis of tyrosinase; the mass ratio of dopamine hydrochloride to paeonol is 2:5; the enzyme-responsive precursor mineral is obtained by coating nano-calcium pyrophosphate with ε-polylysine; the polyethylene glycol doped dopamine modified hydroxyapatite is obtained by surface adhesion modification of hydroxyapatite with polyethylene glycol doped dopamine; and the carbomer is carbomer 940.
[0040] The preparation method of the dopamine-dopamine modified chitosan quaternary ammonium salt includes: preparing 1.5 g / 100 mL chitosan quaternary ammonium salt solution with PBS buffer solution with pH=6.0; preparing dopamine-dopamine mixed solution containing 2 g / 100 mL dopamine hydrochloride and 5 g / 100 mL paeonol with anhydrous ethanol; preparing 0.6 g / 100 mL tyrosinase solution with PBS buffer solution with pH=6.0; under light protection and nitrogen protection, adding the dopamine-dopamine ethanol solution and the tyrosinase solution into the chitosan quaternary ammonium salt solution according to the volume ratio of 100:20:5, and stirring at 37℃ and 300 rpm for 24 h; increasing the temperature to 85℃ to inactivate the enzyme for 10 min; cooling to room temperature, loading into a dialysis bag with a molecular weight cut-off of 3500 Da, using deionized water containing 2% volume ethanol as the dialysis solution, dialyzing for 72 h, and replacing the dialysis solution every 12 h; then dialyzing with flowing deionized water for 8 h; freeze-drying to obtain dopamine-dopamine modified quaternary ammonium chitosan.
[0041] The preparation method of the enzyme-responsive precursor mineral includes: preparing 10 g / 100 mL nano-calcium pyrophosphate suspension with deionized water, filtering with a 0.45 μm filter membrane after ultrasonic dispersion to obtain an inner phase; preparing 2 g / 100 mL ε-polylysine solution with deionized water, and adjusting the pH value to 7.2 with 1M NaOH aqueous solution to obtain an outer phase; under ice water bath and 800 rpm stirring, adding the inner phase into the outer phase according to the volume ratio of 1:1.05, the adding speed is 2 mL / min, and stirring at 600 rpm for 1.5 h; centrifuging to collect the precipitate, washing with ultrapure water for 3 times, and freeze-drying to obtain the enzyme-responsive precursor mineral.
[0042] The preparation method of the polyethylene glycol di-dopamine modified hydroxyapatite includes: preparing 1.0 g / 100 mL nano-hydroxyapatite dispersion liquid with pH 8.5 Tris-HCl buffer solution; adding polyethylene glycol di-dopamine with a mass of 25% of the nano-hydroxyapatite, ultrasonic mixing uniformly, and then stirring at 300 rpm for 30 h under 25℃ and light protection; centrifuging to collect the precipitate, washing the precipitate with ethanol aqueous solution for 2 times, and then washing the precipitate with deionized water for 2 times, and freeze-drying to obtain the polyethylene glycol di-dopamine modified hydroxyapatite.
[0043] The preparation method of the above-mentioned desensitizing drug for enamel repair includes the following steps:
[0044] Deionized water, glycerol, hyaluronic acid-maleimide, paeonol-dopamine modified chitosan quaternary ammonium salt, enzyme responsive precursor mineral, polyethylene glycol di-dopamine modified hydroxyapatite and strontium nitrate were mixed by mass fraction, carboxymethylcellulose was added under stirring, and the stirring was continued to swell, and the pH value was adjusted to 7.0 with triethanolamine, then L-cysteine was added, stirred for 1 min, vacuum degassed, and the drug was obtained.
[0045] Example 3
[0046] A desensitizing drug for enamel restoration, the drug comprising the following raw materials by mass fraction: paeonol-dopamine modified chitosan quaternary ammonium salt 5 parts, enzyme responsive precursor mineral 4 parts, polyethylene glycol di-dopamine modified hydroxyapatite 3 parts, strontium nitrate 1 part, hyaluronic acid-maleimide 2.5 parts, L-cysteine 0.3 parts, carbomer 1.2 parts, glycerol 14 parts and deionized water 72 parts; the pH value of the drug is adjusted to 6.5. Wherein, the paeonol-dopamine modified chitosan quaternary ammonium salt is obtained by modifying chitosan quaternary ammonium salt with paeonol and dopamine hydrochloride under the catalysis of tyrosinase; the mass ratio of dopamine hydrochloride to paeonol is 3:4; the enzyme responsive precursor mineral is obtained by coating nano-calcium pyrophosphate with ε-polylysine; the polyethylene glycol di-dopamine modified hydroxyapatite is obtained by adhering and modifying hydroxyapatite with polyethylene glycol di-dopamine on the surface; the carbomer is carbomer 940.
[0047] The preparation method of the paeonol-dopamine modified chitosan quaternary ammonium salt comprises the following steps: preparing 1 g / 100 mL chitosan quaternary ammonium salt solution with PBS buffer solution of pH=6.5; preparing dopamine-paeonol mixed solution containing 3 g / 100 mL dopamine hydrochloride and 4 g / 100 mL paeonol with anhydrous ethanol; preparing 0.4 g / 100 mL tyrosinase solution with PBS buffer solution of pH=6.5; under light protection and nitrogen protection, adding the dopamine-paeonol ethanol solution and the tyrosinase solution into the chitosan quaternary ammonium salt solution according to the volume ratio of 100:25:3, stirring at 40°C and 200 rpm for 30 h; increasing the temperature to 80°C to inactivate the enzyme for 15 min; cooling to room temperature, loading into a dialysis bag with a molecular weight cut-off of 3500 Da, using deionized water containing 1% volume ethanol as the dialysis solution, dialyzing for 96 h, replacing the dialysis solution every 8 h; then dialyzing with flowing deionized water for 12 h; freeze-drying to obtain paeonol-dopamine modified quaternary ammonium chitosan.
[0048] The preparation method of the enzyme-responsive precursor mineral comprises the following steps: preparing a 5 g / 100 mL nano-calcium pyrophosphate suspension with deionized water, filtering the suspension with a 0.45 μm filter membrane after ultrasonic dispersion, and obtaining an inner phase; preparing a 5 g / 100 mL ε-polylysine solution with deionized water, and adjusting the pH value of the solution to 7.5 with a 0.5 M NaOH aqueous solution to obtain an outer phase; under the condition of ice water bath and 600 rpm stirring, the inner phase is added to the outer phase at a volume ratio of 1:1.2, the adding speed is 1 mL / min, and the stirring speed is 800 rpm for 1 h; the precipitate is obtained by centrifugation, and the precipitate is washed with ultrapure water for 4 times, and then freeze-dried to obtain the enzyme-responsive precursor mineral.
[0049] The preparation method of the polyethylene glycol doped hydroxyapatite comprises the following steps: preparing a 1.5 g / 100 mL nano-hydroxyapatite dispersion liquid with a pH 8.0 Tris-HCl buffer solution; adding 20% polyethylene glycol doped dopamine by mass of the nano-hydroxyapatite, uniformly mixing by ultrasonic, and then stirring at 200 rpm for 35 h under the condition of 30°C and avoiding light; the precipitate is collected by centrifugation, the precipitate is washed with an ethanol aqueous solution once, and then washed with deionized water for 3 times, and then freeze-dried to obtain the polyethylene glycol doped hydroxyapatite.
[0050] The preparation method of the above-mentioned desensitizing drug for tooth enamel repair comprises the following steps:
[0051] Deionized water, glycerol, hyaluronic acid-maleimide, paeonol-dopamine modified chitosan quaternary ammonium salt, enzyme-responsive precursor mineral, polyethylene glycol doped hydroxyapatite and strontium nitrate are mixed according to the mass fraction, and carbomer is added under stirring, and then the mixture is fully swelled by continuing stirring, and the pH value is adjusted to 6.5 by adding triethanolamine, and then L-cysteine is added, and the mixture is stirred for 2 min, and then vacuum degassing is performed to obtain the drug.
[0052] The raw material sources involved in the above examples: the chitosan quaternary ammonium salt was from Xi'an Qiuhuo Biological Technology Co., Ltd. The dopamine hydrochloride was from Nanjing Bemoda Biological Technology Co., Ltd. The paeonol was from Jiangxi Xuesong Natural Medicine Oil Co., Ltd., with a content of 99%. The tyrosinase was from Hubei Rishengchang New Material Technology Co., Ltd. The nano-calcium pyrophosphate was from Hubei Shuaiyan Li Gao Biological Medicine Co., Ltd. The ε-polylysine was from Zhengzhou Bainabio Biological Engineering Co., Ltd. The nano-hydroxyapatite was from Xi'an Mao Nian Biological Technology Co., Ltd., with a particle size D50 of 60 nm. The polyethylene glycol dipolydopamine was from Beijing Jingpin Technology Co., Ltd. The glycerol was from Xi'an Qingyan Biological Technology Co., Ltd., 1,2,3-propanetriol. The hyaluronic acid-maleimide was from Beijing Jingpin Technology Co., Ltd. The carbomer 940 was from Shaanxi Baohe Biological Technology Co., Ltd. The triethanolamine was from Xi'an Taihua Pharmaceutical Technology Co., Ltd. The L-cysteine was from Hebei Chuangzhiyuan Biological Technology Co., Ltd. The above raw materials were all medical or food grade.
[0053] Comparative Example 1
[0054] The difference from Example 1 is that the paeonol-dopamine modified chitosan quaternary ammonium salt is replaced by chitosan quaternary ammonium salt.
[0055] Comparative Example 2
[0056] The difference from Example 1 is that no paeonol is added in the preparation of the paeonol-dopamine modified chitosan quaternary ammonium salt.
[0057] Comparative Example 3
[0058] The difference from Example 1 is that in the preparation of the paeonol-dopamine modified chitosan quaternary ammonium salt, a dopamine-paeonol mixed solution containing 4.5 g / 100 mL dopamine hydrochloride and 2.5 g / 100 mL paeonol is prepared with anhydrous ethanol; that is, the content of dopamine hydrochloride is greater than that of paeonol.
[0059] Comparative Example 4
[0060] The difference from Example 1 is that the enzyme-responsive precursor mineral is replaced by nano-calcium pyrophosphate.
[0061] Comparative Example 5
[0062] The difference from Example 1 is that the polyethylene glycol dipolydopamine modified hydroxyapatite is replaced by nano-hydroxyapatite.
[0063] Comparative Example 6
[0064] The difference from Example 1 is that the paeonol-dopamine modified chitosan quaternary ammonium salt is replaced by a mixture of chitosan quaternary ammonium salt, paeonol and dopamine; and the polyethylene glycol di-dopamine modified hydroxyapatite is replaced by a mixture of nano-hydroxyapatite and polyethylene glycol di-dopamine.
[0065] Comparative Example 7
[0066] The difference from Example 1 is that no hyaluronic acid-maleimide is added in the drug.
[0067] Comparative Example 8
[0068] The difference from Example 1 is that no L-cysteine is added in the drug.
[0069] Comparative Example 9
[0070] The difference from Example 1 is that in the drug, hyaluronic acid-maleimide is 0.5 parts, and L-cysteine is 2 parts.
[0071] Comparative Example 10
[0072] The difference from Example 1 is that in the drug, paeonol-dopamine modified chitosan quaternary ammonium salt is 1 part, and enzyme-responsive precursor mineral is 8 parts.
[0073] Experiment I, dentin tubule occlusion rate detection:
[0074] 1. Preparation of dentin slices: Collecting extracted molar teeth, cutting into dentin slices, polishing with 400, 800, 1200 sandpaper, ultrasonic treatment in 17% EDTA solution for 10 min to completely remove the smear layer, exposing the dentin tubule opening, ultrasonic cleaning with deionized water for 3 times, 5 min each time, and storing in physiological saline for standby.
[0075] 2. Drug treatment: The drug is evenly coated on the surface of the dentin slice with a thickness of 0.5 mm, and incubated in a 37℃, 100% humidity environment for 24 h.
[0076] 3. Detection: The sample is fixed with 2.5% glutaraldehyde, dehydrated with gradient ethanol, critical point dried, and then gold spraying treatment. Randomly select 5 fields (×2000) under SEM, calculate the percentage of the number of effectively occluded tubules in the total number of tubules in each field, and take the average value as the tubule occlusion rate.
[0077] Experiment II, enzyme-responsive mineral release rate determination:
[0078] 1. Release medium: The experimental group is pH 7.4 Tris-HCl buffer containing 1.0 U / mL alkaline phosphatase (ALP); the enzyme-free control group is the same buffer without ALP.
[0079] 2. Test: 0.1 g of drug was placed in 10 mL of release medium, constant temperature at 37°C, 100 rpm shaking. 1 mL was sampled at 1 h, 3 h, 6 h, 12 h (at the same time, supplement with fresh medium of equal volume), and the sample was filtered through a 0.22 μm filter membrane, and then Ca was determined by ICP-OES 2+ concentration, enzyme response cumulative Ca 2+ net release amount = cumulative Ca 2+ release amount of the experimental group - cumulative Ca 2+ release amount of the control group without enzyme.
[0080] Experiment III, Brushing Resistance Test:
[0081] 1. Initial sealing rate uses the data of Experiment I.
[0082] 2. Brushing operation and test: The same batch of samples of Experiment I were fixed on a toothbrush abrasion tester (ISO standard), the bristles were soft nylon brushes, toothpaste slurry (prepared according to ISO 11609:2017), the weight was 200 g, and brushing was performed 5000 times (simulating 2 weeks of tooth brushing). After brushing, the samples were washed with deionized water and dried, and then the sealing rate was detected according to the method of Experiment I. Calculation: Brushing retention rate (%) = (sealing rate after brushing / initial sealing rate) x 100%.
[0083] Experiment IV, Acid Resistance Test:
[0084] 1. Initial sealing rate uses the data of Experiment I.
[0085] 2. Acid erosion operation and test: The same batch of samples of Experiment I were immersed in a pH 4.0 lactic acid solution (0.1 M), constant temperature at 37°C, 50 rpm shaking for 1 min, and then taken out, washed with deionized water, dried, and repeated 5 cycles. After acid erosion, the sealing rate was detected according to the method of Experiment I. Calculation: Acid erosion retention rate (%) = (sealing rate after acid erosion / initial sealing rate) x 100%.
[0086] Each sample was made in 5 parallel samples, and the average test results are shown in Table 1.
[0087] Table 1 Test Results
[0088]
[0089] From the above results, examples 1 to 3 achieve high sealing rate, controlled release and excellent durability through the synergistic effect of multiple components, adhesion, enzyme response mineralization and cross-linking enhancement. (1) The triple synergistic effect of paeonol-dopamine modified chitosan quaternary ammonium salt: the ortho-diphenol group of dopamine forms hydrogen bonds with the hydroxyl groups on the dentin surface, and the positively charged chitosan quaternary ammonium salt is electrostatically adsorbed to the negatively charged dentin, while paeonol enhances antibacterial properties, reduces bacterial erosion of the tooth surface, and improves film stability. (2) Enzyme-responsive precursor mineral: alkaline phosphatase (ALP) uses ε-polylysine-sustained calcium pyrophosphate as a substrate to continuously provide Ca 2+ for mineralization. (3) Polyethylene glycol doped hydroxyapatite: directly fills the dentin tubules, and polyethylene glycol doped dopamine enhances its adhesion to the adhesive layer, reducing shedding. (4) Strontium nitrate: strontium ions bind to collagen within the tubules to form strontium phosphate salt, physically sealing the tubules, and inhibiting nerve potassium ion channels to desensitize. Through scientific proportioning of each component, better repair, desensitization and long-lasting effects are achieved.
[0090] Comparative example 1 (chitosan quaternary ammonium salt instead of paeonol-dopamine modified chitosan quaternary ammonium salt): ordinary chitosan quaternary ammonium salt has no ortho-diphenol group of dopamine, cannot form strong hydrogen bonds with dentin, relies only on electrostatic adsorption, and the film layer is prone to shedding. Without the antibacterial and stabilizing effect of paeonol, the film layer is quickly damaged under friction and acid erosion; Ca 2+ release is not affected: the enzyme-responsive precursor mineral and hydroxyapatite are unchanged, so Ca 2+ release is close to that of example 1.
[0091] Comparative example 2 (no paeonol added in the modification): dopamine provides partial adhesion, but lacks the hydrophobicity and antibacterial effect of paeonol, and the film layer lacks sufficient density; paeonol has broad-spectrum antibacterial properties, and its absence increases bacterial proliferation on the tooth surface, accelerating bacterial metabolic acid production and film layer degradation; paeonol can enhance the film-forming property of chitosan, and its absence increases the brittleness of the film layer, which is prone to cracking during brushing, and the film layer's hydrophobicity and stability decrease, reducing its resistance to brushing and acid. Ca 2+ release shows no significant change.
[0092] Comparative example 3 (dopamine content greater than paeonol): increased dopamine enhances adhesion, but reduced paeonol leads to decreased hydrophobicity and antibacterial properties, and the film layer's hydrophilicity is abnormal; excessive hydrophilic dopamine and insufficient hydrophobic paeonol cause the film layer to easily absorb moisture from oral saliva and swell, making it prone to shedding during brushing; the film layer's quality is inferior to that of the examples, and its chemical stability is insufficient. Excessive dopamine affects the release rate of the mineral from the carrier.
[0093] Comparative Example 4 (enzyme-responsive precursor mineral replaced by nano-calcium pyrophosphate): The nano-calcium pyrophosphate without being coated by e-polylysine is easy to aggregate, difficult to effectively enter the tubule, and has poor sealing effect. The aggregated mineral without coating is easy to be washed or eroded by acid. The aggregated calcium pyrophosphate has poor compatibility and slow release, and it is difficult to form a good enzyme response effect.
[0094] Comparative Example 5 (polyethylene glycol doped hydroxyapatite replaced by nano-hydroxyapatite): The nano-hydroxyapatite without modification is easy to aggregate and has poor dispersibility, which affects the tubule blocking effect. The ordinary hydroxyapatite has no bridging effect of polyethylene glycol dopamine, and cannot be tightly combined with the adhesion layer of modified chitosan quaternary ammonium salt. It is easy to fall off and has poor durability. The enzyme response Ca 2+ release has no significant change.
[0095] Comparative Example 6 (dopamine-modified chitosan quaternary ammonium salt and polyethylene glycol doped hydroxyapatite without modification): The lack of adhesion carrier and functional hydroxyapatite, only physical mixing, increases the aggregation, and the sealing rate is extremely low. The free mixture is not uniform, which also affects the enzyme response Ca 2+ release to some extent. In addition, the adhesion, brush resistance, acid resistance and other durability are poor.
[0096] Comparative Example 7 (without adding hyaluronic acid-maleimide): Hyaluronic acid-maleimide can form a thiol-maleimide cross-linking bond with the thiol group of L-cysteine, enhancing the toughness of the film layer. The lack of cross-linking reaction of maleimide and L-cysteine leads to poor stability of the gel network, and the retention rate significantly decreases after brushing and acid erosion. The enzyme response Ca 2+ release has no significant change.
[0097] Comparative Example 8 (without adding L-cysteine): The lack of thiol-ene click chemistry cross-linking reaction does not strengthen the gel network, and the film layer is loose, which reduces the mechanical and chemical properties. The enzyme response Ca 2+ release has no significant change.
[0098] Comparative Example 9 (unbalanced ratio of hyaluronic acid-maleimide and L-cysteine): Too little maleimide and too much L-cysteine result in an inappropriate cross-linking density, leading to a loose network, which affects the adhesion and durability.
[0099] Comparative Example 10 (dopamine-modified chitosan quaternary ammonium salt is reduced, and the enzyme-responsive precursor mineral is increased):
[0100] The lack of adhesion components leads to weak bonding force between the film layer and dentin, and although the mineral is increased, it is easy to fall off, and the retention rate after brushing and acid erosion is low. The Ca 2+ release is excessive: too much mineral leads to initial burst release, and the controlled release effect is poor.
Claims
1. A desensitizing agent for tooth enamel repair, characterized in that, The medicine comprises the following mass fractions of raw materials: 3-5 parts of dopamine-modified chitosan quaternary ammonium salt, 4-6 parts of enzyme-responsive precursor mineral, 2-3 parts of polyethylene glycol di-dopamine modified hydroxyapatite, 1-2 parts of strontium nitrate, 1.5-2.5 parts of hyaluronic acid-maleimide, 0.3-0.6 parts of L-cysteine, 0.8-1.2 parts of carbomer, 14-17 parts of glycerol and 65-72 parts of deionized water; the pH value of the medicine is adjusted to 6.5-7.0; The dopamine-modified chitosan quaternary ammonium salt is obtained by modifying chitosan quaternary ammonium salt with dopamine hydrochloride and paeonol under the catalysis of tyrosinase; the mass ratio of dopamine hydrochloride to paeonol is (2-3):(4-5); The enzyme-responsive precursor mineral is obtained by coating nano-calcium pyrophosphate with epsilon-polylysine; The polyethylene glycol di-dopamine modified hydroxyapatite is obtained by surface adhesion modification of hydroxyapatite with polyethylene glycol di-dopamine.
2. The desensitizing agent for the restoration of dental enamel according to claim 1, wherein The preparation method of the dopamine-modified chitosan quaternary ammonium salt comprises the following steps: preparing 1g / 100mL-1.5g / 100mL chitosan quaternary ammonium salt solution with PBS buffer solution with pH=6.0-6.5; preparing dopamine-paeonol mixed solution containing 2g / 100mL-3g / 100mL dopamine hydrochloride and 4g / 100mL-5g / 100mL paeonol with anhydrous ethanol; preparing 0.4g / 100mL-0.6g / 100mL tyrosinase solution with PBS buffer solution with pH=6.0-6.5; under light protection and nitrogen protection, the dopamine-paeonol ethanol solution and the tyrosinase solution are added to the chitosan quaternary ammonium salt solution according to the volume ratio of 100:(20-25):(3-5), and the mixture is stirred at 37-40°C; the enzyme is inactivated by heating; the mixture is cooled to room temperature, and then is loaded into a dialysis bag; deionized water containing 1%-2% volume ethanol is used as dialysate, and the dialysis is performed for 72-96 hours; then, the dialysis is performed with flowing deionized water; and freeze-drying is performed to obtain the dopamine-modified chitosan quaternary ammonium salt.
3. The desensitizing agent for the restoration of dental enamel according to claim 2, wherein The stirring is performed at 200-300rpm for 24-30 hours; the enzyme is inactivated by heating to 80-85°C for 10-15 minutes; the molecular weight cut-off of the dialysis bag is 3500Da; the dialysate is replaced every 8-12 hours; and the dialysis with flowing deionized water is performed for 8-12 hours.
4. The desensitizing agent for the restoration of dental enamel according to claim 1, wherein The preparation method of the enzyme-responsive precursor mineral comprises the following steps: preparing a nano-calcium pyrophosphate suspension of 5g / 100mL-10g / 100mL with deionized water, filtering with a filter membrane after ultrasonic dispersion to obtain an inner phase; preparing an epsilon-polylysine solution of 2g / 100mL-5g / 100mL with deionized water, adjusting the pH value to 7.2-7.5 to obtain an outer phase; under the condition of ice water bath and stirring, adding the inner phase into the outer phase according to the volume ratio of 1: (1.05-1.2), and stirring for 1h-1.5h; centrifuging to obtain a precipitate, washing the precipitate with ultrapure water, and freeze-drying to obtain the enzyme-responsive precursor mineral.
5. The desensitizing agent for the restoration of dental enamel according to claim 4, wherein The filter membrane is a 0.45μm filter membrane; the pH value is adjusted by using a 0.5M-1M NaOH aqueous solution; the stirring speed is 600rpm-800rpm; the dropping speed is 1mL / min-2mL / min; and the ultrapure water centrifugal washing is performed for 3-4 times.
6. The desensitizing agent for the restoration of dental enamel according to claim 1, wherein The preparation method of the polyethylene glycol doped polydopamine modified hydroxyapatite comprises the following steps: preparing a nano-hydroxyapatite dispersion liquid of 1.0g / 100mL-1.5g / 100mL with a Tris-HCl buffer solution of pH 8.0-8.5; adding polyethylene glycol doped polydopamine with a mass fraction of 20%-25% of the nano-hydroxyapatite, ultrasonic mixing, and then stirring; centrifuging to collect a precipitate, washing the precipitate, and freeze-drying to obtain the polyethylene glycol doped polydopamine modified hydroxyapatite.
7. The desensitizing agent for the restoration of dental enamel according to claim 6, wherein The particle size D50 of the nano-hydroxyapatite is less than 100nm; the stirring is performed at 25℃-30℃ under light shielding conditions at a speed of 200rpm-300rpm for 30h-35h; and the precipitate is washed once or twice with an ethanol aqueous solution and then twice or thrice with deionized water.
8. The desensitizing agent for the restoration of dental enamel according to claim 1, wherein The carbomer is carbomer 940.
9. The method of claim 1, wherein the desensitizing agent is incorporated into the dental enamel restoration by, The method comprises the following steps: The deionized water, glycerol, hyaluronic acid-maleimide, danpi phenol-dopamine modified chitosan quaternary ammonium salt, enzyme-responsive precursor mineral, polyethylene glycol doped polydopamine modified hydroxyapatite and strontium nitrate are mixed according to the mass fraction, the carbomer is added under stirring, the stirring is continuously performed to sufficiently swell, the pH value is adjusted to 6.5-7.0, then L-cysteine is added, the stirring is performed for 1min-2min, vacuum defoaming is performed, and a drug is obtained.
10. The method of claim 9, wherein the desensitizing agent is a fluoride ion source. The pH value is adjusted by using triethanolamine.
Citation Information
Patent Citations
Antibacterial synergy-mineralization regulation difunctional nano material as well as preparation method and application thereof
CN120713863A
Dental formulation
WO2016135521A1
